Pengaruh Pengalaman dan Kualitas Pelayanan terhadap Loyalitas yang dimediasi Kepuasan Pelanggan: Studi pada Konsumen Warmindo “X” di Kota Malang - Nasharuddin Mas; Dian Candra Dewi; Riris Zahrotul Fauziah (PPIMAN Pusat Publikasi Ilmu Manajemen, 2025)
This study aims to examine the influence of customer experience and service quality on customer loyalty, with customer satisfaction as a mediating variable. Using a quantitative approach and explanatory research method, data was obtained through the distribution of questionnaires to 96 respondents who were selected through purposive sampling techniques and were consumers of Warmindo "X" in Malang City. Data analysis was carried out using the Partial Least Square – Structural Equation Modeling (PLS-SEM) method with the help of the SmartPLS application. The results of the study show that customer experience and service quality have a significant effect on customer satisfaction. Furthermore, customer satisfaction has been proven to have a direct influence on customer loyalty. However, the quality of service does not have a direct influence on customer loyalty, thus showing the important role of the mediation variable. Customer satisfaction has been proven to be able to mediate the relationship between customer experience and service quality to customer loyalty. These findings are in line with the Expectancy-Disconfirmation theory, SERVQUAL, and Customer Experience Theory, which emphasize the importance of consumer perception of quality and experience in shaping satisfaction and loyalty. The practical implications of this study encourage Warmindo "X" managers in Malang City to consistently improve the quality of service and create a pleasant and memorable dining experience. These efforts are believed to increase satisfaction and maintain consumer loyalty in the long term, especially in the midst of increasingly competitive competition in the culinary industry. In addition, this research also makes a theoretical contribution in understanding the mediation mechanism in the relationship between service marketing variables. Further research is expected to explore additional variables such as price, dining atmosphere, or service personalization that may also affect customer loyalty.